EFEKTIVITAS PEMBERIAN AROMATERAPI LEMON TERHADAP PENURUNAN EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - Sri Juliani; Ramini harahap, Novy; Nurrahmaton; Bunga Camelia Putri Tarigan (Maternity and Neonatal : Jurnal Kebidanan, 2024)
Pregnant women who have emesis gravidarum perform just naturally; for first-trimester pregnancies, this happens six weeks after the first day of the last menstrual period. Giving lemon aromatherapy, an aromatherapy preparation made from lemon, can be used to treat emesis gravidarum in addition to pharmaceutical and non-pharmacological treatments. by administering lemon aromatherapy for seven days straight during emesis gravidarum. of this study aimed to determine the effectiveness of lemon aromatherapy to reduce emesis gravidarum in first trimester pregnant women at Romauli Clinic Medan. The design of this study is Pre-Experimental research using One Group Pretest Posttest approach. The population in this study were pregnant women who experienced emesis gravidarum at Romauli Clinic with 20 pregnant women. The sampling technique used Purposive Sampling with a sample of 12 respondents according to the inclusion and exclusion criteria. Using the Paired T-Test test to determine the effectiveness of lemon aromatherapy on emesis gravidarum mothers. The results showed the average frequency level of emesis gravidarum pre test (6.75), and the post test results were (3.66) with a difference of (3.08). Based on the Paired Sample T Test test, the Sig value was 0.000 <0.05. The conclusion shows that, in Romauli Clinic Medan in 2023, using lemon aromatherapy can lessen first-trimester morning sickness in pregnant women. It is suggested that pregnant women and health professionals, in particular, employ lemon aromatherapy as an alternative and natural therapy for the non-pharmacological treatment of emesis gravidarum.